Young New Zealanders' Consumption of Television Fiction Programs: An Exploratory Study of Young People's Reception Habits. Issue 1 (August 2014) - Fedele, Maddalena
This article presents part of the findings of an exploratory study of young people's consumption of television fiction programs, carried out in Aotearoa New Zealand. The paper focuses on young people's reception habits, describing those practices within the rest of their leisure activities. A questionnaire was administered to a convenience sample of 225 first-year Victoria University of Wellington students aged 17–30. Among the main results, young people's predilection for television fiction must be emphasised. Even if watching television is not one of the more frequent leisure activities for those surveyed, most of them report watching at least one or two different fiction programs every day, especially by themselves or with friends, and in domestic common spaces. They also show some multimedia and multi-tasking consumption strategies – such as watching fiction programs through different media, such as the TV set, DVDs and the internet – and carrying out simultaneous activities while watching.